Coalescence of Water Drops in Water-ULSD Dispersions via Electrowetting - Bandekar, Ashish; G. Chase, George (Journal of Coating Science and Technology, 2016)
Coalescence of water droplets is an important phenomenon in many industrial applications. One approach for coalescing water droplets is by applying an external voltage across the drops. Coalescence occurs when spreading and motion of the drops due to the electrical field brings the drops into contact. Electrowettable surfaces were prepared with poly(styrene-co-methyl methacrylate) as the dielectric film and Fluropelâ„¢ as the hydrophobic surface layer. The surface of a stainless steel disk was coated in a way that the dielectric coating layer thickness varied with radial position with minimum thicknesses at the center and at the outer edge of the disk and a maximum at an intermediate radial position of the disk surface. The thickness gradient influenced the droplet movement and contributed to the coalescence. Two disks were assembled with a thin slit between the disks. Emulsions of water droplets in ultra low sulfur diesel fuel were pumped through the thin slit. Experiments showed significant increase in drop sizes when the disks were electrified compared to non-electrified disks.